Altıncı ve Yedinci Sınıf Öğrencilerinin Hoca Ahmed Yesevî Algıları / Sixth and Seventh Graders’ Perceptions of Khoja Ahmad Yassawi - Kılcan, Bahadır; Akbaba, Bülent; Gülbudak, Burcu (Journal of History Culture and Art Research, 2017)
Abstract The purpose of this research is to determine sixth and seventh graders’ perceptions of Khoja Ahmad Yassawi, who was among Turkish-Muslim thinkers, covered in the sixth and seventh grades social sciences curriculum. To this end, the metaphors produced and the pictures/cartoons drawn by the students about Khoja Ahmad Yassawi were examined. Qualitative research designs were employed in the research. The study group consists of 237 sixth and seventh graders educating in Mamak district of Ankara province in the spring semester of the 2015-2016 academic year. The data obtained from the participants were analyzed and interpreted via content analysis. The participants were found to have the following perceptions of Khoja Ahmad Yassawi: “informing, advisory”, “guiding, illuminating”, “showing the truth, providing benefit”, and “leaving a mark, esteemed”. Öz Bu araştırmada, sosyal bilgiler 6 ve 7. sınıf öğretim programında yer alan Türk-İslam mütefekkirlerinden Hoca Ahmed Yesevi’nin altıncı ve yedinci sınıf öğrencileri tarafından nasıl algılandığının belirlenmesi amaçlanmıştır. Bu amaç doğrultusunda; öğrencilerin Hoca Ahmed Yesevi’ye ilişkin geliştirdikleri metaforlar ve çizdikleri resim/karikatürler incelenmiştir. Nitel araştırma deseninde gerçekleştirilen araştırmanın çalışma grubunu 2015-2016 eğitim öğretim bahar döneminde Ankara ili Mamak ilçesinde öğrenim gören 237 altıncı ve yedinci sınıf öğrencisi oluşturmaktadır. Katılımcılardan elde edilen verilerin çözümlenmesinde ve yorumlanmasında içerik analizi kullanılmıştır. Araştırma sonucunda katılımcıların, Hoca Ahmed Yesevi’yi; “bilgi sağlayan, öğüt veren”, “yol gösteren, aydınlatan”, “doğruyu gösteren, fayda sağlayan” ve “iz bırakan, değerli olan” şeklinde algıladıkları görülmektedir.